15‐1: A Novel Compression Algorithm Application for De‐Mura Compensation of AMOLED Panel - Zuo, Yini; Lee, Eunho; Lee, Kyoungwon; Kim, Changman; Shang, Fei; Qiu, Haijun (SID International Symposium Digest of technical papers, 2023)
A novel compression algorithm was adopted to compress De‐mura compensation data, and the compression process was described in detail. The compensation performance of 2x2 compression case is close to the original 2x2 case, and performs better than 4x4 compensation case with the same file size as it. Apart from that, the combination of De‐mura and compression also performs the good compensation results at low gray as well as low display brightness. The better performance, small space occupancy and low power consumption were reached simultaneously, indicating the effective application of combination of compression algorithm and De‐mura algorithm.